Encyclopedia of the Third Reich - Snyder, Louis L. (Louis Leo), 1907-1993. (Ware, Hertfordshire : Wordsworth Editions, 1998)
This reference book covers the rise of National Socialism to the fall of the Third Reich in May 1945, and also carries selected entries on the Weimar Republic which proceeded Hitler and on the Bonn Republic which succeeded him.
Includes bibliographical references (pages 389-410).
Keywords: Third Reich -- Dictionaries; Third Reich; 1933-1945; National socialism -- Dictionaries; National socialism; Germany -- History -- 1933-1945 -- Dictionaries; Germany; dictionaries; Dictionaries; History; Dictionaries